Entrepreneurial mindset transformation: Synergy of entrepreneurship and creativity education for female students in Malaka Regency - Saragih, Fernando; Gie, Emilia; Simbolon , Gallex (Priviet Social Sciences Journal, 2025)
This study aims to analyze the influence of entrepreneurship education and creativity on the entrepreneurial interest of female students in Malaka Regency, East Nusa Tenggara, Indonesia. The background of this study is based on the high poverty rate and suboptimal utilization of entrepreneurial potential in the area. The study used a quantitative approach with a survey method of 72 respondents selected incidentally. The research instrument was a questionnaire with a five-point Likert scale, including 20 statements for the entrepreneurship education variable and 30 statements for the creativity variable. Data analysis was conducted using multiple linear regression with the classical assumption test, t-test, F-test, and coefficient of determination. The results show that entrepreneurship education has a positive but insignificant effect on entrepreneurial interest, whereas creativity has a positive and significant effect. Simultaneously, both variables had a significant effect, contributing 51.2% to the variation in entrepreneurial interest. These findings indicate that creativity is a dominant factor in shaping the entrepreneurial interest of female students, while entrepreneurship education requires strengthening methods and contextual support to be effective. This study recommends the development of an applicable curriculum, business incubation programs, and funding and mentoring support to build an adaptive and inclusive entrepreneurial ecosystem in the local area.